EFEK TANAMAN HERBAL SEBAGAI OBAT PENYAKIT DIABETES MELITUS: A LITERATURE REVIEW - Rahmi Syukra Fadilla; Abdullah, Dessy; Riki Nova (Nusantara Hasana Journal, 2025)
Diabetes mellitus (DM) is a chronic disease whose prevalence continues to increase every year. According to predictions from the World Health Organization (WHO), the number of diabetes sufferers in Indonesia will increase from 8.4 million in 2000 to around 21.3 million in 2030 (Widiastuti et al., 2022). Uncontrolled diabetes can cause various serious complications, such as heart disease, kidney damage, blindness, and amputation. Therefore, effective management of diabetes mellitus is very important to prevent worse health impacts. One alternative approach that is increasingly popular is the use of herbal plants, which have been shown to have the potential to lower blood glucose levels and help manage diabetes. This study aims to summarize herbal plants that have been scientifically proven to have an effect on controlling blood glucose levels in people with diabetes mellitus. The results of this literature review are expected to provide new insights for researchers and medical practitioners in developing more natural and affordable diabetes treatments.